Genetic and epigenetic characterization of the tumors in a patient with a tongue primary tumor, a recurrence and a pharyngoesophageal second primary tumor - Ilda P. Ribeiro; Francisco Marques; Leonor Barroso; Jorge Miguéis; Francisco Caramelo; André Santos; Maria J. Julião; Joana B. Melo; Isabel M. Carreira (Molecular Cytogenetics, 2017)
Abstract Background The choice of therapeutic modality for oral carcinoma in recurrent or second primary tumors remains controversial, as the treatment modalities available might be reduced by the treatment of the first tumor, and the overall survival is lower when compared with patients with a single or first tumor. Identifying biomarkers that predict the risk of relapse and the response to treatment is an emerging clinical issue. Case presentation A Caucasian 49-years-old man was treated with chemotherapy followed by chemoradiotherapy for a primary left side tongue tumor, achieving a complete response. After 49-months of follow-up, a local recurrence was diagnosed. After 3 months, a second primary tumor at the pharyngoesophageal region was detected. Genomic and epigenetic characterization of these three tumors was performed using array Comparative Genomic Hybridization, Multiplex Ligation-dependent Probe Amplification (MLPA) and Methylation Specific MLPA. Results The three tumors of this patient shared several imbalances in all chromosomes excluding chromosomes 9, 20 and 22, where genes related to important functional mechanisms of tumorigenesis are mapped. The shared genomic imbalances, such as losses at 1p, 2p, 3p, 4q, 5q, 6q, 7q, 8p, 10p, 11q, 12p, 12q, 13q, 15q, 16p, 16q, 17p, 17q, 18q, 19p, 19q, 21q and Xp and gains at 3q, 7q, 14q and 15q showed a common clonal origin for the diagnosed relapses. We identified some chromosomal imbalances and genes mapped in the chromosomes 2, 3, 4, 6, 7, 11, 14, 17, 18 and 22 as putative linked to chemoradioresistance and chemoradiosensitivity. We also observed that gains in short arm of chromosomes 6, 7, 8 and 18 were acquired after treatment of the primary tumor. We identified losses of VHL gene and promoter methylation of WT1 and GATA5 genes, as predictors of relapses. Conclusions A common clonal origin for the diagnosed relapses was observed and we identified some putative candidate biomarkers of prognosis, relapse risk and treatment response that could guide the development of management strategies for these patients.